Normal concrete to polymer concrete bond strength: mohr-coulomb theory - Hussin, Mohd. Warid (2015)
This paper discusses an experimental study conducted to evaluate the bonding strength between normal concrete (NC) and polymer concrete (PC) substrate. Ground palm oil fuel ash (GPOFA) was incorporated as micro-filler in this polymer concrete (PC-GPOFA) to investigate its effect on bonding strength. As comparisons, PC containing others filler were prepared, i.e., PC incorporating calcium carbonate (PC CaCO3), silica sand (PC Sand), and unground POFA (PC UPOFA) filler. Two tests were conducted to investigate the bonding between two substrates - slant shear and splitting tensile tests. After critical condition surface (smooth surface) was prepared, the effect of bonding was determined using mohr-coulomb theory. Overall results indicated that PC incorporating GPOFA improved the bonding to normal concrete. This result indicates that the bonding strength of NC to PC at critical condition is affected by self-adhesion of polymer concrete to the normal concrete. The self-adhesive characteristic of polymer concrete to normal concrete can be easily identified in mohr-coulomb analysis. All-in-all, the PC incorporating ground POFA could improve the bonding to the normal concrete.